2015
DOI: 10.1021/om501231k
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic PCN Palladium Pincer Complexes. Probing the Hemilability through Reactions with Nucleophiles

Abstract: A series of unsymmetrical PCN pincer ligands (1-(3-((di-tert-butylphosphino)­methyl)­phenyl)-N,N-dialkylmethanamine) were cyclometalated with palladium to generate a series of new PCN supported Pd­(II) chloro complexes, (PCN)­PdCl (4–6), where alkyl = methyl, ethyl, and n-propyl, which were fully characterized by NMR spectroscopy and X-ray crystallography. The N,N-dimethyl complex 4 reacts with methyl lithium to give the corresponding methyl and dimethyl complexes (PCN)­PdMe (12) and Li­[(PCN)­PdMe2] (13), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 53 publications
0
40
0
Order By: Relevance
“…Table 3 also show that there is no significant difference in the catalytic activity of unsymmetrical and symmetrical pincer palladacycles. This may be because the trans-influence [30] and/or hemilability [69,70] of the pincer ligands (and complexes) do not affect the Pd-Cl and/or Pd-C bonds in the key TM and RE steps of the pre-catalyst activation for catalysis.…”
Section: Effect Of Substituents On the Catalytic Activity Of The Novementioning
confidence: 99%
“…Table 3 also show that there is no significant difference in the catalytic activity of unsymmetrical and symmetrical pincer palladacycles. This may be because the trans-influence [30] and/or hemilability [69,70] of the pincer ligands (and complexes) do not affect the Pd-Cl and/or Pd-C bonds in the key TM and RE steps of the pre-catalyst activation for catalysis.…”
Section: Effect Of Substituents On the Catalytic Activity Of The Novementioning
confidence: 99%
“…This can lead to different physical and chemical properties of the donor ligand arms, resulting in preferential decoordination of one of the ligand arms, providing the opportunity to fine tune the catalytic activity of unsymmetrical pincer palladacycles [18][19][20][21]. An excellent example by Wendt and co-workers reported the hemilabile nature of nitrogen and phosphorus donor atoms by reacting with a strong nucleophile (MeLi) [22]. The results showed that the nitrogen donor atom arm decoordinated from the Pd center, while the phosphorus donor atom arm remained coordinated to the Pd center (Scheme 1).…”
Section: Figurementioning
confidence: 99%
“…Scheme 1. Reaction of unsymmetrical pincer palladacycles with MeLi showing the hemilability of the nitrogen donor atom arm by Wendt et al [22].…”
Section: Figurementioning
confidence: 99%
“…Despite the fast expansion of the field of pincer complexes, [1][2][3][4][5][6][7][8][9] those with unsymmetric pincer ligands have received limited attention compared to the symmetric ones in part as a result of the long synthetic routes used to prepare the unsymmetric ligand scaffolds. [10][11][12][13][14][15][16][17][18][19][20][21][22][23] However, unique reactivity has sometimes been documented for these ligands, and for PCN ligands such reactivity includes selective C-C vs. C-H bond activation and hemilability through de-coordination of the weak side arm of the unsymmetric pincer ligand. [10][11][12]18] Also increased reactivity in CO 2 insertion has been reported.…”
Section: Introductionmentioning
confidence: 99%